2014
DOI: 10.1016/j.parkreldis.2014.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive functions in Parkinson's disease: Relation to disease severity and hallucination

Abstract: This is the study to demonstrate the cognitive impairments in PD patients using WAIS-III. Visuospatial dysfunction might be caused by decrease in rCBF in the parietal and occipital lobes and dorsolateral prefrontal cortex. The severity of cognitive impairments in PD patients was correlated with disease severity and hallucinatory episodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 19 publications
(18 reference statements)
3
10
0
Order By: Relevance
“…Besides sensory and motor functions (Herrero, Barcia, & Navarro, 2002), (Wakamori et al, 2014). The present ASL data strengthen the evidence for the hemodynamics of the thalamus as a potential biomarker for the development of cognitive impairment in PD.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Besides sensory and motor functions (Herrero, Barcia, & Navarro, 2002), (Wakamori et al, 2014). The present ASL data strengthen the evidence for the hemodynamics of the thalamus as a potential biomarker for the development of cognitive impairment in PD.…”
Section: Discussionsupporting
confidence: 80%
“…Poor performance in semantic fluency tests has been associated with a higher risk of developing dementia (Williams‐Gray et al, ). A recent SPECT study found that cognitive functions in PD patients were positively correlated with CBF in the thalamus (Wakamori et al, ). The present ASL data strengthen the evidence for the hemodynamics of the thalamus as a potential biomarker for the development of cognitive impairment in PD.…”
Section: Discussionmentioning
confidence: 99%
“…Vaden et al showed that elevated cingulo-opercular activity provides word-recognition benefit showing that the cingulo-opercular network is not only important as a somatosensory area but is also fundamental for cognitive function (Vaden et al, 2013). Of note, hallucinations have been closely connected to cortical dysfunction in PD (Wakamori et al, 2014). Parkinson's disease is related to aging and is accompanied by a decrease in cognitive and motor capacities.…”
Section: Discussionmentioning
confidence: 99%
“…They are prevalent in both psychiatric disorders, such as schizophrenia (60-80%) 2 and bipolar disorder (BD 10-23%) 3 , and neurodegenerative diseases, such as Parkinson's disease (PD; 22-38%) 4 , dementia with Lewy Bodies (DLB; 80%) 5 , and Alzheimer's disease (AD; 13-18%) 6 , as well as in other psychiatric and neurological disorders, and among the general population (4.5-12.7%) 7 . Irrespective of diagnosis, the presence of hallucinations marks an increased risk of adverse outcomes, such as reduced likelihood of recovery in schizophrenia 8 , more severe cognitive deficits in PD 9 , increased mortality in AD 10 , increased suicidal behaviour in adults with psychosis 11 , and transition to later mental illness in children and young adults 12,13 . Although hallucinations are often distressing, they may also be benign or contribute to meaningful personal experiences 14,15 .…”
Section: Introductionmentioning
confidence: 99%